Synthesis of silica nanoparticles to enhance the fire resistance of cement mortars - Vaz-Ramos, Joana; Santiago, Aldina; Portugal, António; Durães, Luísa (Fire Research, 2019)
Silica nanoparticles are known to enhance the strength and durability of cementitious materials, due to their nanofilling effect and their high pozzolanic reactivity. They also have the potential to improve their thermal properties and fire resistance. However, these improvements are highly dependent on the nanoparticles’ characteristics. In this work, silica nanoparticles were prepared by sol-gel reaction and a design of experiments with four factors was used to conclude about the parameters that have more influence in the synthesis of these nanoparticles and, thus, optimize this process and the particles’ properties. Using a lower ethanol/water, higher hydrolysis and condensation time and higher volume of catalyst, the smallest particle size was obtained (118 nm). The effect of the incorporation of these silica nanoparticles into cement mortars was studied in terms of density and thermal conductivity of these mortars, after curing at room temperature. The presence of silica nanoparticles led to an increase in density and decrease of thermal conductivity. The mortars were also exposed to high temperature, which originated a significant reduction ( 50%) in their thermal conductivity.